Smart Evaluation and Integrated Design in Regional Development. Territorial Scenarios in Trentino, Italy di Grazia Brunetta - Paolinelli, Gabriele (Ri-Vista. Research for landscape architecture, 2016)
The book Smart Evaluation and Integrated Design in Regional Development. Territorial Scenarios in Trentino, Italy presents the outcomes of the application of the Territorial Integrated Evaluation (TIE) methodology in the Autonomous Province of Trento (APT). The TIE application aimed at defining integrated territorial scenarios. This experience – that is the result of a consultancy given by the Politecnico di Torino to the APT – is an interesting case of landscape integration into sectorial policies (retail policies in particular) so as promoted by the European Landscape Convention.